A multi-band antenna for mobile handset - Abdeslam Kabbour Hanzaz, Zakaria (2007)
Conventional microstrip antennas in general have a conducting patch printed on a grounded microwave substrate, and have the attractive features of low profile, light weight, easy fabrication, and conformability to mounting hosts. Microstrip antennas however have a narrow bandwidth, and bandwidth enhancement is usually demanded for practical applications. In addition to being broadband, they should be capable of operating in multiple frequency bands too. Compactness of structure is another feature desired in present-day mobile communication systems in order to meet the miniaturization requirements of mobile units. Thus, mobile phones antennas require reduction in size and broadband operation for compatibility with different standards essentially operating in different frequency bands. This project reviews the techniques used to incorporate these two essential features to a conventional microstrip antenna. Planar Inverted-F Antenna has been developed and the information acquired from these techniques is appropriately used to explain the design of operation for mobile phones. The quarter-wavelength Planar Inverted-F Antenna (PIFA) combines the use of a slot, shorted parasitic patches and capacitive loads to achieve multi-band operation. The result is a compact structure capable of broadband operation in six different frequency bands used by four standards – GSM900 (Global System for Mobile), GPS (Global Position System), DCS1800 (Digital Cellular Systems), PCS1900 (Personal Communication Systems), UMTS2000 (Universal Mobile Telecommunication Systems) and WLAN2400 (Wireless Local Area Network).